Anxiety in Pregnant Women During Pandemic Covid-19 - Nurya Viandika; Ratih Mega Septiasari (Universitas Muhammadiyah Semarang, 2021)
The Covid-19 virus pandemic can cause various manifestations, especially in risk groups, one of which is pregnant women. Pregnancy during a pandemic would be a factor that is anxiety pregnant women which can be impact for babies, like premature, Low Birth Weight, and also depression postpartum. The purpose of this study was to describe the level of anxiety of pregnant women during pandemic Covid-19 at the Jaya Kusuma Husada Clinic Malang, East Java Indonesia. The study was conducted from November to December 2020 and is a descriptive study with total sampling using a questionnaire given to pregnant women. Fifty-three pregnant women filled out forms and the data were analyzed using frequency and proportion tables. The results showed that 2% experienced severe anxiety, 32% had moderate-severe anxiety, 42% had moderate anxiety, 23% had mild anxiety and the remaining 2% of mothers had normal. The coronavirus pandemic is causing anxiety to pregnant women. Pregnant women would easily feel the feeling of something that will happen to them and their children also need to avoid negative impacts on the mother and fetus.